Pentingnya Pengelolaan Manajemen Keuangan dan Model Penganggaran Pendidikan - Muhammad Ibnu Faruk Fauzi (Journal Innovation In Education, 2023)
Education is very important for all humans. Education can be successful if there is good management. The role of education management is very important in an educational institution. Management is basically nothing new in human life, as well as in a management education is needed. Education management can cover a variety of things, one of which is financial management. Because, with good financial management in institutions will increase the efficiency of education so that the achievement of educational goals will soon be realized. Urgency School financial management is very important to classify school needs. Then there is an urgency for financial management and a clear and appropriate budgeting model that will affect school operations and education in these schools. The purpose of this study is to find out how the Urgency of Financial Management and the Education Budgeting Model are applied to find out how supervision is in financial management. Data collection is in the form of observations from various existing sources. The method used is a review article. The results of this study show that the results of the urgency and budgeting model carried out by managing school finances in carrying out the budget plan have been going very well. This is indicated by several activity plans that are realized in accordance with expectations, namely transparent, accountable, effective and efficient.